Analysis of diversity of macrobenthos in mangrove ecosystems as a bioindicator of pollution of the Kalianget coastal area - Ferdiansyah, Akhmad; Ali, Mahrus (Generasi Biologi Indonesia, 2022)
Macrobenthos is a biological resource of water that lives on the bottom of the waters with characteristics that have a high level of sensitivity to changes in environmental quality as a bioindicator of pollution and environmental quality. The purpose of the study was to determine macrobenthos diversity as an indicator of pollution in the Kalianget coastal mangrove forest. Descriptive research with random sampling method with squared transects. Data collection through observation of macrobenthos populations. Research results a) the greatest diversity of macrobenthos of the class Crustaceans obtained 9 species, class Gastropods 5 species, class Bivalves found 3 species and from class Polychaeta found 1 species. b) The Macrobenthos Diversity Index on the Kalianget coast is 1.084539 with the category of moderate macrobenthos diversity, has moderate community stability and polluted waters but is still within the threshold that living things can tolerate.Diversity; Index diversity; Macrobenthos; Mangrove ecosystems